Plan de mejoramiento de la Empresa Funtein S.A., ubicada en San Antonio de Pichincha, Ecuador - Cajas Caballero, Gracia María (2015)
FUNTEIN SA is a company dedicated to the development and marketing of products in cast iron, with over thirty years of experience in the market. In search of further growth, it now requires an improvement plan. The diagnosis established that: the administrative area requires strategic planning and proper delegation of duties; the marketing area needs a plan to increase sales and promote the product; the area of production and operations, while its more organized, it demands politics and procedures for the management of the inventory. The strengths include: extensive experience in the market, compliance with environmental regulations; availability of equipment in good condition; major customers in the government sector. There are weaknesses such as: an inaccessible experienced workforce; absence of a marketing plan; mission and vision is not clearly defined...